Assessing the economic impacts of post-harvest fisheries losses in Malawi. (September 2020) - Torell, Elin C.; Jamu, Daniel M.; Kanyerere, Geoffrey Z.; Chiwaula, Levison; Nagoli, Joseph; Kambewa, Patrick; Brooks, Alan; Freeman, Peter
Highlights: In 2017, the Malawian fishing industry contributed US 454 million (7.2%) to the GDP. Significant quality losses (43–69%) occur at all fisheries value chain nodes. Quality losses are not proportionately affecting the economic loss, which is <10% Low pricing sensitivity of existing products drives the low economic loss. Quality improvements produce partial economic gains and consumer health benefits. Abstract: This paper presents the findings from a qualitative and quantitative fisheries value chain and post-harvest loss study conducted in four Malawian lakes: Malawi, Malombe, Chilwa and Chiuta. The research found that the estimated total value of the fisheries value chain was US 454 million in 2016 – or 7.2% of the projected 2017 GDP. This is over 2.5 times the previously reported (Government of Malawi, 2017) beach landing site value. The study found that 43%, 54% and 69% of fish have physical and quality losses at the beach, processing and marketing nodes, respectively. However, high quality loss is not proportionately affecting economic loss. The fisheries value chain experiences less than 10% annual economic losses mainly due to low pricing sensitivity of existing products. The overall economic losses are nine percent, being highest at the beach node (19.3%) and smallest at the market node (2.1%). The main reason for this unusual relationship is that pricing is not sensitive to quality, which means that almost all types of quality of product is sold resulting in a recorded relatively low overall physical loss of 4.1%. An important conclusion of the assessment is that even though the economic losses are relatively modest in relation to the total value, the quality losses, which range between 43% and 69% depending on the node, indicate that the potential for health impacts and nutritional value loss are high throughout the value chain. Value chain improvements are recommended to provide economic and nutritional benefits for end-users and value chain actors.